THEORETICAL ANALYSIS OF THREE PARAMETERS DETERMINING A THERMAL POWER CALIBRATION METHOD FOR THE TRIGA RESEARCH REACTOR - Žagar, doc. dr. Tomaž (Journal of Energy Technology, 2024)
Analytical analysis and calculation of factors relevant to the calorimetric power calibration method in the TRIGA research reactor are given. The calibration of nuclear instrumentation in the TRIGA re- search reactor is routinely done using a thermal power calibration method. The accuracy of the calorimetric thermal power calibration method depends on the accuracy of the thermal properties of the research reactor pool. The most important properties of the reactor pool and the corresponding factors are reactor pool heat capacity, factor describing heat loss to the concrete wall, and the factor describing heat loss to the air above the pool. In this paper, these factors are first analytically calculated using only basic physical principles. The calculated values are compared to experimental values reported in the litera- ture, and good alignment is observed. This paper also has substantial educational value; it demonstrates that simple and basic analytical physics calculations can produce meaningful and useful results and can be validated against mea- sured data obtained directly from experiments.